DSM-5 Trichotillomania: Perception of Adults With Trichotillomania After Psychosocial Treatment. Issue 2 (2nd April 2016) - Houghton, David C.; McFarland, Colleen S.; Franklin, Martin E.; Twohig, Michael P.; Compton, Scott N.; Neal-Barnett, Angela M.; Saunders, Stephen M.; Woods, Douglas W.
Abstract : Objective : Trichotillomania (TTM) is associated with significant embarrassment and is viewed negatively by others. A potentially important outcome variable that is often overlooked in treatment for TTM is appearance and social perception. Method : The present study tested whether participants in a randomized controlled trial (RCT) of psychotherapy for TTM are viewed more positively by others. All participants in the trial were photographed at baseline and posttreatment. Three treatment responders and three treatment nonresponders were selected randomly for the present study. Several healthy controls were also photographed in a similar manner. Undergraduate college students ( N = 245) assessed whether they would reject the person socially, whether the individual has a psychological or medical problem, and attractiveness. Results : Individuals with TTM were viewed more negatively than healthy controls at baseline, but treatment responders showed positive improvements on all perceptions relative to nonresponders. While treatment responders were still perceived more poorly than controls on social rejection and perceptions of problems at posttreatment, responders where rated no differently than controls on attractiveness at posttreatment. Conclusions : The results suggest that persons with TTM who respond to treatment are rated by others as significantly improved in appearance, but they might be still stigmatized or socially rejected.